Scanning Acoustic Microscope for 3D imaging - DYNOWSKI, Krzysztof; LITNIEWSKI, Jerzy; NOWICKI, Andrzej (Archives of Acoustics, 2008)
A new Acoustic Microscope operating at the frequency up to 200 MHz and allowing for visualization of the internal structures of materials was developed. The system was built basing on the commercially available components and the self-designed acoustic lenses. The dedicated software was developed to control the process of 3D RF-data acquisition, processing and presenting in 2D cross-sections or 3D surface rendering mode. This article describes the technical principles of the constructed microscope and presents the reconstructed images of the designed test-probe and of the integrated circuit.